Identifikasi Faktor Penyebab terjadinya Kenakalan Remaja menggunakan Metode Multi Factor Evaluation Process (MFEP) - Limbong, Riswan; Siregar, Kristian (LPPM UNIKA Santo Thomas Medan, 2019)
Juvenile delinquency is a very actual problem in almost every country including Indonesia. Outbreaks of cases of juvenile law violations such as robbery, robbery, fighting, theft, possession of sharp weapons and misuse of narcotics as well as various other legal violations. With so many cases of violations of the law it is illustrated that in the era of complete human development, it is expected that adolescents have the rights and obligations and responsibilities to develop the nation and state but many do unlawful acts. The Multifactor Evaluation Process (MFEP) method is a quantitative method that uses